Driving factors of Deforestation in Indonesia: A case of Central Kalimantan - ELY SUSANTO; NANIK LESTARI; MAHARANI HAPSARI; KRISDIYATMIKO KRISDIYATMIKO (Universitas Muhammadiyah Yogyakarta, 2018)
As one of countries which has the large tropical forests in the world and the largest in ASEAN, Indonesia has been facing serious deforestation problems. Eventhough some scholars have found causes of the deforestation and have tried to give solutions, however, identifications of deforestation causes are still worth studying as the deforestation still becomes an important issue in Indonesia. This study tries to extend and explore the causes of deforestation in Central Kalimantan, one of Provinces in Indonesia which has been facing the highest deforestation problem caused by many factors. This study applied a qualitative approach. Data were collected by using interview and focus group discussions. It involved about 27 informants representing 14 organizations including goverment officers and non-governmental organization leaders such as WALHI,AMAN, Save Our Borneo, Yayasan Bentang Borneo, Ampuh, TUK Jakarta, Greenpeace, SIEJ, SPKS, Sawit Watch, Forest Watch Indonesia, Mongabay, Institute Dayakologi, LINK-AR Borneo, WWF and Academia as informants. The study found that as a socio political construct, deforestation in Indonesia emerges at the intersection between the biophysical changes of the politically defined forest and the political economic struggles around access and control over forestland resources by domestic and international actors. Hardly is a given issue, the term deforestation itself is still subject to debate as state definition of deforestation is continuously being challenged by the definition developed by civil society members. Deforestation, in many of its aspects, is also associated with governance failure and complex political economic settings that shape its emergence.